Delegation in Hiring: Evidence from a Two-Sided Audit - Bo Cowgill; Patryk Perkowski (CESifo GmbH, 2024)
Firms increasingly delegate job screening to third-party recruiters, who must not only satisfy employers' demand for different types of candidates, but also manage yield by anticipating candidates' likelihood of accepting offers. We study how recruiters balance these objectives in a novel, two-sided field experiment. Our results suggest that candidates' behavior towards employers is very correlated, but that employers' hiring behavior is more idiosyncratic. Workers discriminate using the race and gender of the employer's leaders more than employers discriminate against the candidate's race and gender. Black and female candidates face particularly high uncertainty, as their callback rates vary widely across employers. Callback decisions place about two thirds weight on employer's expected behavior and one third on yield management. We conclude by discussing the accuracy of recruiter beliefs and how they impact labor market sorting.
Keywords: M51; C93; J71; 330; hiring; recruiting; discrimination; field experiments